Effectiveness of Control Dashboard Utilization in Managing Multiple Events at Telkom Corporate University - Haq, Najwa Maulita; Pranata, Rici Tri Harpin (IHSA Institute, 2025)
The development of digital technology encourages organizations to adopt a more integrated management system, including in the management of large-scale events or multiple events. This study aims to examine the implementation and effectiveness of the use of control dashboards in the management of multiple events at Telkom Corporate University, an institution under the Telkom Group that routinely organizes various training and development programs. The research method used is a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation studies. The results of the study indicate that the control dashboard plays an important role in facilitating the planning, monitoring, and evaluation of events in real-time through features such as event overview, database events, event calendar, and feedback analysis. This system not only improves operational efficiency but also strengthens team collaboration and the quality of decision-making. This study concludes that the use of control dashboards significantly optimizes the process of managing multiple events at Telkom Corporate University. These findings are expected to contribute to the development of real-time data-based management information systems in the corporate education and training sector